Adaptive finite-time bipartite consensus for second-order multi-agent systems with antagonistic interactions - Zhao, Lin; Jia, Yingmin; Yu, Jinpeng (Systems & control letters, 2017)
This paper is concerned with the adaptive finite-time bipartite consensus problems for networked second-order multi-agent systems with antagonistic interactions and unknown external disturbances. A signed undirected graph is used to describe the interactions among agents. For the leaderless case, continuous nonlinear distributed protocols with adaptive update laws are given, which can not only guarantee the bipartite steady-state errors of any two agents converge to a small region in finite time, but also eliminate the chattering problem. Then, the proposed algorithm is extended to solve the adaptive finite-time bipartite consensus tracking problem for leader–follower case by designing distributed finite-time estimator. Simulation example is included to show the effectiveness of the presented methods.